Development of a new classification for in vivo diagnosis of duodenal epithelial tumors with confocal laser endomicroscopy: A pilot study. Issue 2 (24th November 2015) - Nonaka, Kouichi; Ohata, Ken; Ichihara, Shin; Ban, Shinichi; Hiejima, Yoshimitsu; Minato, Yohei; Tashima, Tomoaki; Matsuyama, Yasushi; Takita, Maiko; Matsuhashi, Nobuyuki; Takasugi, Rumi; Neumann, Helmut
Abstract : Background and Aim: Confocal laser endomicroscopy (CLE) has been established for in vivo diagnosis of various gastrointestinal diseases. However, validated criteria for confocal diagnosis of duodenal tumors do not exist. Therefore, the aim of the present pilot study was to develop a novel classification for in vivo optical diagnosis of duodenal tumors using CLE. Methods: Consecutive patients with duodenal tumorous lesions were included. First, an initial classification system was developed which was then validated. Histopathology was used as a reference standard. Results: A simple classification system for in vivo diagnosis of duodenal epithelial tumors using CLE was developed. Sensitivity, specificity, and accuracy were 90%, 100%, and 97%, respectively. Positive and negative predictive values were calculated as 100% and 96%. The kappa coefficient representing consistency was 1 between observers and within each observer. Conclusion: A new classification for in vivo diagnosis of duodenal epithelial tumors using confocal imaging has been developed. The new classification system allows adequate prediction of histology and could therefore be used to guide subsequent therapy of duodenal lesions.